Membangun Ketangguhan dan Adaptasi Transformatif: Kasus Pengurangan Risiko Bencana Banjir di Jakarta - Tri Mulyani Sunarharum (REKA RUANG, 2020)
Flooding has been increasingly seen as a 'real problem' in Jakarta since 2013. Since then, the Provincial Government of DKI Jakarta has urged the implementation of various mega infrastructure developments, including increasing the capacity of the Ciliwung River. However, the project was hampered by differences in perceptions and understanding between the community and the government regarding the risk of flooding and efforts to reduce risk. This study aims to analyze how governments, non-governmental organizations and vulnerable communities understand flood risk and how they cooperate in the decision-making process for flood risk reduction. This research also examines efforts to increase resilience and transformative adaptation that have been carried out, as well as evaluates policies and plans related to flood disaster risk reduction in DKI Jakarta. This research focuses on case studies of disaster risk reduction in high flood risk areas in the Kampung Melayu, DKI Jakarta. Empirical research provides qualitative data on the influence of collaborative mechanisms in decision-making processes related to flood risk reduction efforts. In addition, this research has the potential to increase knowledge transfer on increasing resilience in urban planning implementation related to disaster risk reduction, as well as increasing transformative adaptation to the impacts of climate change.